A Taylor drop rising in a liquid co-current flow. (November 2017) - Direito, F.J.N.; Campos, J.B.L.M.; Miranda, J.M.
Highlights: Flow patterns of Taylor drops rising in co-current vertical flow are determined. Balance between co-current flow and gravity forces is crucial for drop behavior. Stabilization distance below the drop depends on the drop Reynolds number. Drop velocity and continuous phase velocity are linearly related. Viscosity ratio causes a deviation from the gas-liquid case. Abstract: The present work presents a numerical study on the behavior of isolated liquid Taylor drops rising in vertical tubes with co-current heavier continuous phase. Numerical simulations were performed with a previously validated model, implementing Volume of Fluid method in an axisymmetric geometry. Detailed flow patterns and drop shapes are provided and discussed for several conditions. The balance between gravity effect and velocity of the continuous phase flow was found to have a great influence in the flow patterns observed. The increase of inertial effects, due to the increase of Eo number and the co-current velocity, leads to the occurrence of closed recirculations below the drops. Furthermore, the continuous phase stabilization distance below the drop is a function of the drop Reynolds number. Drop and continuous phase velocities relationship was studied. A viscosity ratio related term was appended to a pre-existing correlation. The flow in the absence of gravity was also studied. Results demonstrate that micro-scale flow is a lower limit to the cases studied in the present work and suggest that the viscosity ratio affects mainly the inertial part of the drop velocity.